2019
DOI: 10.1021/acsomega.9b00792
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation Kinetics of Polyethylenimine-based Adsorbents Used for the Capture of Low Concentration CO2

Abstract: CO 2 emission is generally regarded as the major contributor to global climate change, and polyethylenimine (PEI)-based CO 2 adsorbents are promising materials for the capture of low concentration CO 2 . This paper deals with the deactivation kinetics of PEI-based CO 2 adsorbents used for the capture of low concentration CO 2 . EA and TG analyses demonstrated that thermal degradation and O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…proposed a thermooxidative degradation model for the degradation of PEI as tracked by losses in CO 2 capacity after various oxidation times. The developed model suggested that an O 2 -induced PEI deactivating in simulated air takes on second order kinetics with an activation energy of 74 kJ/mol . This method, however, accounts for the reaction progression based on mass loss, which may not be a comprehensive view due to the complexity of the reactions.…”
Section: Introductionmentioning
confidence: 99%
“…proposed a thermooxidative degradation model for the degradation of PEI as tracked by losses in CO 2 capacity after various oxidation times. The developed model suggested that an O 2 -induced PEI deactivating in simulated air takes on second order kinetics with an activation energy of 74 kJ/mol . This method, however, accounts for the reaction progression based on mass loss, which may not be a comprehensive view due to the complexity of the reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative stability of PEI-functionalized adsorbents has attracted much research attention. 130,132,254,383,385,390,391,395 Oxidative degradation depends on the operating temperature in addition to the oxygen partial pressure. For example, 55 wt% PEI/SBA-15, as the first PEI-modified adsorbent being reported focusing on the oxidative stability according to our best knowledge, lost 22% and 70% of CO 2 uptake after accelerated oxidative treatment under carbon-free air flow at 90 °C and 100 °C, respectively.…”
Section: Avoidance Of Oxidative Degradationmentioning
confidence: 99%
“…The weight loss under a simulated air flow is lower, indicative of the incorporation of oxygen in the material due to oxidative degradation. The loss of CO 2 capacity at 50 °C under thermal and oxidative degradation conditions after ∼2700 h is 2.0 and 3.6% respectively, while the weight loss is 1.0 and 1.2% respectively (Figure 3 26 ). The curves of thermal and oxidative degradations over time do not show a distinctive shape.…”
Section: Deactivation Kinetics Of Polyethylenimine-based Adsorbents U...mentioning
confidence: 99%
“…Si et al reported on simulated air oxidation of BPEI in the total absence of H 2 O and CO 2 . Reaction times were up to 3000 h, and a temperature window from 50 to 80 °C was used …”
Section: Introductionmentioning
confidence: 99%